Research about listening: everyday music interactions - Krause, Amanda Elizabeth (Curtin University, 2014)
The aim of this PhD is to better understand the place that music occupies in everyday, modern life. Specifically, the three sections of this thesis address the most notable aspects of music is experienced as a consequence of the digital revolution, namely [1] how music fits in with other contemporaneous activities; [2] how music is accessed and selected; and [3] a focus on music practices on social media.